2013
DOI: 10.1016/j.celrep.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

TRPV3 Channels Mediate Strontium-Induced Mouse-Egg Activation

Abstract: SUMMARY In mammals, calcium influx is required for oocyte maturation and egg activation. The molecular identities of the calcium-permeant channels that underlie the initiation of embryonic development are not established. Here, we describe a Transient Receptor Potential (TRP) ion channel current activated by TRP agonists that is absent in TrpV3−/− eggs. TRPV3 current is differentially expressed during oocyte maturation, reaching a peak of maximum density and activity at metaphase of meiosis II (MII), the stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
94
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 79 publications
(91 reference statements)
9
94
1
Order By: Relevance
“…We hypothesized that transient receptor potential (TRP) channels were likely candidates for this role because these cation conducting channels are expressed in all types of cells and can contribute to a wide array of cellular responses (reviewed in [33]). TRPV3 current has been demonstrated in mouse eggs, but this current was not detected in GV oocytes [34]; therefore, TRPV3 is unlikely to mediate spontaneous Ca 2+ influx in GV oocytes. Mice lacking all seven TRPC channels have been generated and shown to be viable and fertile [35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that transient receptor potential (TRP) channels were likely candidates for this role because these cation conducting channels are expressed in all types of cells and can contribute to a wide array of cellular responses (reviewed in [33]). TRPV3 current has been demonstrated in mouse eggs, but this current was not detected in GV oocytes [34]; therefore, TRPV3 is unlikely to mediate spontaneous Ca 2+ influx in GV oocytes. Mice lacking all seven TRPC channels have been generated and shown to be viable and fertile [35].…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that Ca V 3.2 contributes to Ca 2+ influx to support ER store accrual and robust Ca 2+ oscillations, but females lacking Ca V 3.2 are merely subfertile, indicating that this channel does not function alone either [27]. TRPV3 channels are present in mouse eggs and contribute to Sr 2+ -mediated parthenogenesis; however, Trpv3 −/− females are fertile and their eggs have normal Ca 2+ oscillations following fertilization, indicating that these channels do not have a required physiological function in eggs [34]. It will be interesting to begin investigating the effects of knocking out these channels in combination to overcome inherent limitations of studies using pharmacological inhibitors and ultimately determine the mechanisms of Ca 2+ influx that support egg activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonselective, Ca 2þ -permeant transient receptor potential (TRP) channels are intriguing candidates to be these mechanosensitive channels [69,84,86,88]. However, little is known about TRP channels in mammalian eggs; only TRPV3 is thus far characterized in mouse eggs, and its role in normal egg activation is unclear (but TRPV3 does appears to mediate Sr 2þ influx in SrCl 2 -induced artificial egg activation) [89]. It is very likely that multiple channels could mediate Ca 2þ influx into eggs.…”
Section: Discussionmentioning
confidence: 98%
“…Various methods have been employed to induce artificial calcium oscillations in mammalian oocytes in vitro and thereby provoke oocyte activation and embryo development. Electrical pulses [18], calcium ionophore [19], and strontium [20] are typically used as parthenogenetic agents, and it has been demonstrated that electrical pulses and calcium ionophore generate a single calcium elevation, whereas multiple calcium oscillations are induced by normal fertilization or strontium [20]. Moreover, there is some evidence that procaine is able to disregulate cytoplasmic calcium rise(s) in female gametes.…”
Section: Introductionmentioning
confidence: 98%